EVOLUTION OF SCIENTIFIC THOUGHT ABOUT THE ESSENCE OF DEPRECIATION AND ITS SIGNIFICANCE IN THE DEPRECIATION POLICY OF THE ENTERPRISE - OVOD, LARYSA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the economic category of "depreciation" in the works of scientists and regulations: different positions, approaches, concepts, aspects and options. The main shortcomings about the role of depreciation in modern business conditions are emphasized: 1) neglect of the importance of the process of depreciation of fixed assets in the enterprise; 2) mixing the concepts of "depreciation", "depreciation deductions", "wear"; 3) appropriation of depreciation of functions not peculiar to it. There are eight main positions in the works of scientists about the economic essence of depreciation, but none of these positions corresponds to the role of depreciation in modern conditions. The main approaches to the interpretation of depreciation by scientists are as follows: 1) depreciation – a monetary expression of depreciation of fixed assets; 2) depreciation – the process of transferring the cost of depreciation of fixed assets to the cost of production; 3) depreciation – the method of accounting; 4) depreciation – an investment resource and a means of accumulating funds for further renewal of means of labor. The variety of approaches to the interpretation of the term "depreciation" made it possible to systematize and combine certain approaches in the concept of depreciation. The main conceptual and specific approaches the author considers the legislative, classical, including economic and accounting, as well as tax. The classical approach is based on the concept of depreciation and impairment of fixed assets, reimbursement of their value and reproduction. Based on the analysis of concepts and aspects of depreciation, a new approach to determining the nature of depreciation under market conditions has been formed. Today, depreciation of fixed assets is an interactive tool for strategic management and optimization of the tax potential of the enterprise.